Purificação, imobilização e caracterização bioquímica de lipase produzida por Penicillium sect. Gracilenta CBMAI 1583 em cultivo submerso - Turati, Daniela Flavia Machado [UNESP] (2015)
Lipases (triacylglycerol acyl hydrolases, EC 3.1.1.3) are ubiquitous enzymes. However microbial enzymes stand out on the current industrial scenario, due to their wide spectrum of application. In this sense, prospection of new sources of lipases with distinct characteristics is an important research field. Among microorganisms, fungi are being explored for enzyme production, because they secrete high amounts of proteins to extracellular medium that are generally regarded as safe for human health. This work is inserted in this context once it aims to purify and to characterize the main biochemical properties of lipase produced by the filamentous fungus Penicillium sect Gracilenta CBMAI 1583, isolated from soil under Atlantic Rainforest and yet not studied in respect to this enzyme. Optima pH and temperature of activity were 4.0 and 70 °C, respectively, for both crude and purified lipase. Activation energys of hydrolysis of pNPP catalyzed by crude and purified lipase were 27.01 and 8.77 KJ.mol-1, respectively. Crude lipase was more stable to temperature (T(1/2) of 1.5 h, 6.3 and 2.3 min at 50, 60 and 70 °C, respectively) and less stable to pH (stable only at pH 5.0 to 7.0), while purified lipase showed the opposite behavior (T(1/2) of 8.5 min, 33.6 and 15.4 s at the same temperatures; and stable at pH 2.0 to 8.5). Regarding the stability in presence of surfactants, anionic detergents destabilized the protein structure with consequent loss of activity, while nonionic detergents at 1 % (w/v) activated the enzyme. Lipase was purified to homogeneity by one step, through a hydrophobic interaction chromatography at low ionic strength using the Phenyl Sepharose resin, as revealed by SDS-PAGE. By this strategy it was possible to recover 80.8 % of initial activity and achieve a purification factor of 516.1. Enzyme molecular mass was estimated to be 52.9 kDa by SDS-PAGE and 85.3 kDa by size exclusion chromatography, suggesting the formation of ...